Diferença da complacência intracraniana entre homens e mulheres após inclinação negativa da cabeça em indivíduos saudáveis - Michaliski, Eloisa Soares (Universidade Federal de São Carlos, 2024)
The NASA has resumed space explorations after half a century, with the crewed mission to Mars being the longest to date. Medical studies aim to improve the travel conditions for selected astronauts, considering that space travel affects vital systems in the human body. Alterations in the central nervous system and visual impairments have been reported, with differences between sexes. Intracranial Pressure (ICP) is a relevant concern during space travel, as the absence of Earth’s gravity increases ICP and intracranial volume, impacting vision, balance, motor coordination, memory, and reasoning. Monitoring ICP is essential to assess human adaptation during space travel, considering these differences. Objective: To identify whether there is a difference in PIC morphology (P2/P1 ratio) between men and women at rest in the supine position and after head-down tilt at -6°. Methodology: 42 healthy and active individuals of both sexes, aged 25 to 45 years, who met eligibility criteria, were included. Blood tests and Cardiopulmonary Exercise Testing were performed, followed by non-invasive PIC monitoring in three positions: pre-tilt, tilt, and post-tilt. Statistical analysis: Normality (Kolmogorov-Smirnov) and homogeneity (Levene) tests were applied. The Friedman test was used to verify differences in the P2/P1 PIC ratio among supine, -6° tilt, and post-tilt positions, as well as differences between sexes during all three positions. A significance level of 5% and a confidence interval of 95% were considered for all analyses. Results: In this study, the initial hypothesis that both groups would have an increased P2/P1 ratio after -6° tilt was confirmed, although in different magnitudes. The significant difference in PIC waveform morphology occurred in the male group, observed both in the pre-tilt (p=0.038) and post-tilt (p=0.038) moments, contrary to initial expectations (Figure 3). Additionally, when comparing both groups, the tilt moment did not show significant differences (p=0.292). Conclusion: No significant differences were found within the female (p=1.000) and male (p=1.000) groups, but the comparison between female and male groups during the supine position and post-tilt at -6° revealed a surprising significant difference in PIC waveform morphology in the male group.
Difference in intracranial compliance between men and women after head-down tilt in healthy individuals
Keywords: Hipertensão intracraniana; Inclinação de cabeça para baixo; Medicina aeroespacial; Microgravidade; Simulação de microgravidade; Sistema nervoso central; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL